2022
DOI: 10.3390/jcm12010116
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of (R)-[11C]PK11195 PET/MRI for Spinal Cord-Related Neuropathic Pain in Patients with Cervical Spinal Disorders

Abstract: Activated microglia are involved in secondary injury after acute spinal cord injury (SCI) and in development of spinal cord-related neuropathic pain (NeP). The aim of the study was to assess expression of translocator protein 18 kDa (TSPO) as an indicator of microglial activation and to investigate visualization of the dynamics of activated microglia in the injured spinal cord using PET imaging with (R)-[11C]PK11195, a specific ligand for TSPO. In SCI chimeric animal models, TSPO was expressed mainly in activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…First, we found that sciatic nerve injury furthers the expression of the TSPO in the DRG and the spinal cord. The overexpression of the mitochondrial translocator protein (TSPO) is linked to several pathological conditions like neuropathic pain, cancer, and traumatic brain injury [ 53 , 54 ]. Besides being a marker for neuroinflammation, some evidence suggests that overexpression of TSPO indicates abnormal mitochondrial activity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, we found that sciatic nerve injury furthers the expression of the TSPO in the DRG and the spinal cord. The overexpression of the mitochondrial translocator protein (TSPO) is linked to several pathological conditions like neuropathic pain, cancer, and traumatic brain injury [ 53 , 54 ]. Besides being a marker for neuroinflammation, some evidence suggests that overexpression of TSPO indicates abnormal mitochondrial activity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of efficacy of the latter in the study by Ndao and collaborators [ 79 ] might be, at least in part, explained by the small sample size consisting of patients with different diagnoses and treatment histories. Moreover, the lack of reduction of pain intensity using essential oils in some studies can be due to a late start of treatment which can act only as palliative when chronic pain is established, especially for CIPN, while it should be prevented with earlier therapy [ 100 , 101 ]. Therefore, to provide good certainty of the body of evidence for the management of cancer-related pain using essential oils, it is necessary to establish for natural products a step-by-step preclinical-to-clinical pathway to provide a rationale for effective and safe use.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of delayed MRI (>2 weeks after injury) was suggested in a prospective study; however, determining the need for surgery and implementing it as soon as possible are both difficult tasks. Other objective assessments, such as machine learning [79][80][81], biomarkers [82][83][84], and novel imaging technologies [85][86][87], are required to evaluate neurological prognoses and treatment strategies. The increased signal intensity grade in delayed MRI displayed a significantly negative correlation with the JOA score; however, this correlation was absent in acute MRI.…”
Section: Discussionmentioning
confidence: 99%